Activity Engagement Among Older Adult Spousal Caregivers. (28th July 2017) - Queen, Tara L; Butner, Jonathan; Berg, Cynthia A; Smith, Jacqui
Abstract: Objective: Spousal caregiving can have strong implications for health and wellbeing given the strain and burden associated with the role. Maintaining activity engagement is important for late-life health and wellbeing, and may be a possible contributing mechanism to caregiver health and wellbeing. This paper examined longitudinal changes in activity engagement and asks how spousal caregiving status and caregiver age related to longitudinal activity engagement in a sample of older adults. Method: Data from four waves of the Health and Retirement study were used to model associations between periods of being a spousal caregiver, age, and engagement in physical, social, self-care, passive, and novel information processing activities over a 6-year period. Results: Caregiving status was associated with declines in physical activity engagement over time. Older age was associated with fewer physical and more self-care and passive activities. Discussion: Caregivers' declines in participation in physical activities may be an important indicator for preservation of health and management of caregiving stress.